ViPS: A novel visual processing system architecture for medical imaging. (September 2017) - Hussain, Tassadaq
Highlights: Developed a low-power and high-performance medical visual processing system (ViPS). ViPS takes images with complex data structures from medical imaging interfaces. It manages complex images by using on-chip Specialized Medical Memory. To process the application ViPS uses heterogeneous multi-core processors. ViPS provides easy to use programming model for medical applications. Abstract: Imaging has become an essential tool in modern medicine science. Numerous powerful platforms to register, store, analyze and process medical imaging applications appear in recent years. In this article, we have designed an advanced visual processing system (ViPS) that stores and processes complex and multi-dimensional medical imaging application. The ViPS provides a user-friendly programming environment and high-performance architecture for data acquisition, registration, storage, analysis and performs segmentation, filtering, and recognition of complex real-time complex and multidimensional medical images or videos. The proposed architecture is highly reliable concerning cost, performance, and power. ViPS is designed and evaluated on a Xilinx Virtex-7 FPGA VC707 Evaluation Kit. The performance of ViPS is compared with the Heterogeneous Multi-Processing Odroid XU3 board and GPU Jetson TK1 Embedded Development Kit with 192 CUDA cores based graphic systems. In comparison to the Heterogeneous Multi-core and GPU based Graphics systems, the results show that ViPS improves 2.4 and 1.4 times system performance respectively, for iridology application. While executing real-time complex images reconstruction at 2× and 1.25× of higher frame rate, the ViPS achieves 15.2× and 5.26× of performance improvement while running various image processing algorithms. The ViPS gets 3.01× and 1.13× of speedup for video processing algorithms and draws 1.55 and 2.27 times less dynamic power.